Clinical and Electrophysiological Outcome Measures of Patients With Post-Infectious Neurological Syndromes Related to COVID-19 Treated With Intensive Neurorehabilitation - Avenali, Micol; Martinelli, Daniele; Todisco, Massimiliano; Canavero, Isabella; Valentino, Francesca; Micieli, Giuseppe; Alfonsi, Enrico; Tassorelli, Cristina; Cosentino, Giuseppe (Frontiers in Neurology, 2021)
Background. Coronavirus disease 2019 (COVID-19), due to Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection, is typically featured by fever, cough, and shortness of breath, often leading to acute respiratory failure. However, the spectrum of clinical pictures is wide and can also include neurological symptoms. Para-infectious or post-infectious neurological syndromes (PINS), caused by an inflammatory response against the central and/or peripheral nervous system, have been reported in the context of COVID-19. In these cases, the recovery of neurological damage and the clinical outcome after an intensive neurorehabilitation are largely unknown. Material and methods. We describe baseline and follow-up features of 5 patients with PINS associated with COVID-19: three patients with polyradiculoneuropathy and two with myelitis. After completing the acute neurological treatments in the intensive care unit, patients underwent a personalized multidisciplinary rehabilitation program. An in-depth clinical, functional and electrophysiological assessment at baseline and at 3- and 6-month follow-up was carried out. Results. Among patients with polyradiculoneuropathy, the electrophysiological evaluation at baseline disclosed an acute inflammatory demyelinating polyradiculoneuropathy (AIDP) in two patients, and an acute motor sensory axonal neuropathy (AMSAN) in the third patient. At follow-up, the electrophysiological features improved in one subject with AIDP and were comparable to baseline in the remaining two cases. The clinical assessment after neurorehabilitation disclosed a global recovery and full independency in walking and in daily living activities in one patient with AIDP and a mild improvement in the other two cases. Of the two subjects with myelitis, the baseline electrophysiological examination showed a prolonged central motor conduction time, which normalized in one patient whereas improved in the other patient at follow-up. The neurorehabilitation led to a substantial clinical improvement in both subjects. Discussion and conclusions. The clinical recovery after neurorehabilitation in patients with PINS related to SARS-CoV-2 infection seems to be largely variable. In our small case series, subjects with polyradiculoneuropathy had a poorer prognosis as compared to patients with myelitis. The clinical course largely paralleled the follow-up electrophysiological findings. This is the first study to describe clinical and electrophysiological aspects along with medium-term outcome in patients with COVID-19-related neurological manifestations who underwent intensive rehabilitation program.